Editorial Vol17 no3 - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to the September 2018 (Vol 17, No 3) issue of the Scottish Journal of Residential Child Care (SJRCC). It was in September 2002 that Professor Andy Kendrick launched SJRCC as a hard copy, bi-annual publication. Sixteen years later, we are still going, now in digital form and with four issues this year. Andy retired from the University of Strathclyde at the end of June, but will have continuing connections, one of which will be to remain a member of the editorial board with the title of Editor Emeritus. We send Andy our very best wishes for a long, happy and action-packed retirement.